Herbicide programs for control of glyphosate-resistant canola (Brassica napus) in glyphosate-resistant soybean. (13th August 2020) - Mierau, Allyson; Kurtenbach, Moria E.; Johnson, Eric N.; Gulden, Robert H.; Weber, Jessica D.; May, William E.; Willenborg, Christian J.
Abstract: Glyphosate-resistant (GR) canola is a widely grown crop across western Canada and has quickly become a prolific volunteer weed. Glyphosate-resistant soybean is rapidly gaining acreage in western Canada. Thus, there is a need to evaluate herbicide options to manage volunteer GR canola in GR soybean crops. We conducted an experiment to evaluate the efficacy of various PRE and POST herbicides applied sequentially to volunteer GR canola and to evaluate soybean injury caused by these herbicides. Trials were conducted across Saskatchewan and Manitoba in 2014 and 2015. All treatments provided a range of suppression (>70%) to control (>80%) of volunteer canola. All treatments with the exception of the glyphosate-treated control reduced aboveground canola biomass by an average of 96%. As well, canola seed contamination was reduced from 36% to less than 5% when a PRE and POST herbicide were both used. Moreover, all combinations of herbicides used had excellent crop safety (<10%). All PRE and POST herbicide combinations provided better control of volunteer canola compared with the glyphosate-only control, but tribenuron followed by bentazon and tribenuron followed by imazamox plus bentazon provided solutions that were low cost, currently available (registered in western Canada), and had the potential to minimize development of herbicide resistance in other weeds.